Collecting and organising multimedia1 components for the development of educational DVDs and multimedia clips for grade 10 history: The French Revolution – some practical guidelines (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Today’s learners are born in a multimedia world and they feel quite comfortable in an electronic learning environment. !erefore South Africa, as the rest of the world, had to respond to the pressure and challenges posed by the information revolution. Although research shows that there is an increase in the availability of computers for teaching and learning, it does not necessary mean a growth in the use and integration of Information and Communication Technologies (ICTs) in the learning and teaching of subjects in South African schools. For Social Sciences it was an unacceptable low 22% in 2000. A lack of resources for use by teachers and learners is indicated as one of the main factors, preventing teachers from using computers in teaching and learning. The educational DVD and multimedia clips can be used as an exciting interactive resource in the integration of multimedia in the Social Sciences classroom when teaching and learning the French Revolution in History, Grade 10. !is article gives an overview with some practical guidelines on the process followed in the development and construction of the concept text and also the collecting and organisation of the multimedia components for the DVD and multimedia clips
Keywords: History teaching and learning; Information and Communication Technology (ICT); Multimedia; Multimedia elements